Land Suitability and Proposed Land Utilization of Selaru Island, West Southeast Moluccas Regency for Development Food Crops - Sirappa, Marthen Pasang; Waas, Edwen Donald; Susanto, Andriko Noto (JOURNAL OF TROPICAL SOILS, 2016)
The study was conducted in Selaru Island, West Southeast Moluccas Regency in an area of 32,217 ha. The research objective was to determine the land suitability and proposed land utilization of Selaru Island for development of food crops. The results showed that Selaru Island has a rather suitable (S2) and marginally suitable (S3) for six crops (upland rice, corn, peanuts, mungbeans, sweet potato, and caladium) covering an area of 19,330 ha and not suitable permanent (N2) for the six crops covering an area of 3,905 ha, while the area of 8,982 ha partly classified accordingly (S3) to plant upland rice and calladium and partially classified as not suitable (N1 and N2) for corn, peanuts, mungbeans, and sweet potatoes. The main limiting factor to the primary land use for food crops in Selaru Island, West Southeast Moluccas Regency among others are the temperatures (the average annual temperature is high), rooting medium (soil solum is shallow), nutrient retention (soil pH is rather alkaline to alkaline), erosion hazard level is moderate, and terrain (wave, rocks on the surface of the soil, and rock outcrop).The proposed land utilization of Selaru Island for food crops based on land suitability classes are (1) food crops of upland-1 with the main commodities of corn, mungbeans, uwi/kumbili and caladium an area of 5,299 ha, (2) food crops of upland-2 with the main commodities of upland rice, uwi/kumbili and caladium an area of 8,982 ha, and (3) food crops of upland-3 with the main commodities peanuts and mungbean an area of 14,031 ha. Development of food crops in Selaru Island need to consider the priority scale factor, the level of compliance, and social culture of the local community.Keywords: Food crops, land suitability, limiting factor, proposed land utilization, Selaru Island